1989
DOI: 10.1073/pnas.86.9.3199
|View full text |Cite
|
Sign up to set email alerts
|

Heparin suppresses the induction of c-fos and c-myc mRNA in murine fibroblasts by selective inhibition of a protein kinase C-dependent pathway.

Abstract: Heparin is a complex glycosaminoglycan that inhibits the proliferation of several cell types in culture and in vivo. To begin to define the mechanism(s) by which heparin exerts its antiproliferative effects, we asked whether heparin interferes with the expression of the growth factor-inducible protooncogenes c-fos and c-myc. We show that heparin suppressed the induction of c-os and c-myc mRNA by serum in murine (BALB/c) 3T3 fibroblasts. Using purified mitogens, we further show that suppression was most marked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
75
2

Year Published

1992
1992
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(79 citation statements)
references
References 38 publications
2
75
2
Order By: Relevance
“…It is known, for example, that heparin inhibits the PKC-␣-dependent pathway of mitogenesis in smooth muscle cells and fibroblasts, but because it does not directly affect PKC activity or the phosphorylation step, it is believed that the heparin block is distal to the activation of PKC. 56 On the other hand, there are other cellular responses elicited by PMA, such as stimulation of phospholipase D, which can occur independently of PKC. 57 Therefore, further work is needed to elucidate the nature of the mechanism(s) involved in the release and redistribution of TFPI in ECs in culture.…”
Section: Lupu Et Al Effect Of Heparin On Tfpi In Cultured Ecs 2257mentioning
confidence: 99%
“…It is known, for example, that heparin inhibits the PKC-␣-dependent pathway of mitogenesis in smooth muscle cells and fibroblasts, but because it does not directly affect PKC activity or the phosphorylation step, it is believed that the heparin block is distal to the activation of PKC. 56 On the other hand, there are other cellular responses elicited by PMA, such as stimulation of phospholipase D, which can occur independently of PKC. 57 Therefore, further work is needed to elucidate the nature of the mechanism(s) involved in the release and redistribution of TFPI in ECs in culture.…”
Section: Lupu Et Al Effect Of Heparin On Tfpi In Cultured Ecs 2257mentioning
confidence: 99%
“…al., 1989 ;Reilly et al, 1989;Pukac et al, 1990) . The antiproliferative response was not associated with a decrease in the level of inducible protein kinase C (PKC) activity (Wright et al, 1989;Pukac et al, 1990) suggesting that the intracellular GAG blocked events distal to PKC. Wright et al (1989) and Pukac et al (1990) found that the effects of heparin on cell proliferation, induced by TPA or serum, correlates with attenuated levels of cfos and c-myc mRNA.…”
mentioning
confidence: 99%
“…The antiproliferative response was not associated with a decrease in the level of inducible protein kinase C (PKC) activity (Wright et al, 1989;Pukac et al, 1990) suggesting that the intracellular GAG blocked events distal to PKC. Wright et al (1989) and Pukac et al (1990) found that the effects of heparin on cell proliferation, induced by TPA or serum, correlates with attenuated levels of cfos and c-myc mRNA. The expression of these immediate early, or competence class genes, including cjun, is known to be stimulated by various mitogens and growth factors Kelly et al, 1983 ;Greenberg and Ziff, 1984;Kruijer et al ., 1984;Mdller et al, 1984;Greenberg et al, 1985 ;Verma, 1986;Gilman et al ., 1986;Almendral et al, 1988;Chiu et al, 1988;Lamph et al, 1988;Curran and Franza, 1988;Verma and Sassone-Corsi, 1989;Vogt and Bos, 1989), and to precede the onset of protein synthesis required for entry into S phase or the development ofa more differentiated cellular phenotype .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The early G 1 block observed in this work may result from effects of heparin on cell cycle regulatory molecules other than p27 kip1 . For example, the induction of c-Fos and c-Myc in murine fibroblasts (76) and c-Fos induction in mesangial cells (77,78) is blocked by heparin. In addition, heparin has been shown to inhibit cell cycle by inhibition of multiple pathways such as mitogen activated protein kinase (MAPK), calmodulin-dependent protein kinase II, and protein kinase C (PKC).…”
Section: Fig 5 Heparin Treatment Of Vsmc Increases the Half-life Ofmentioning
confidence: 99%